Gastric submucosal microdialysis in the detection of rat stomach ischemia--a comparison of the 3H2O efflux technique with metabolic monitoring - Cibicek, Norbert; Zivna, Helena; Vrublova, Eva; Cibicek, Jaroslav; Cermakova, Eva; Palicka, Vladimir (Physiological measurement, 2010)
Microdialysis has been utilized for nutritive blood flow measurements, but both the advantages and disadvantages of various approaches have not been evaluated in parallel in the stomach yet. Our aim was to compare the (3)H(2)O efflux technique with biochemical monitoring during temporary celiac artery occlusion in anesthetized rats. Microdialysis probes were implanted in the gastric submucosa and perfused with (3)H(2)O; samples were analyzed for β-activity, glucose, lactate, pyruvate and glycerol. Gastric mucosa and plasma were subjected to morphometry and analysis of myeloperoxidase, total thiols and lactatdehydrogenase. The most dramatic responses to ischemia were observed in lactate/pyruvate and lactate/glucose (%) ratios (6.1-9.3×, p < 0.0001); the changes in (3)H(2)O efflux and glycerol were less pronounced (1.1-1.7×, p < 0.0001 and < 0.01, respectively). (3)H(2)O efflux correlated best with the lactate/glucose ratio and glucose alone (r = 0.693 and -0.681, respectively, p < 0.0001). A correlation was also found between plasma lactatdehydrogenase and relative glycerol release (r = 0.600, p < 0.05). Myeloperoxidase, lactatdehydrogenase and histology score were increased by ischemia/reperfusion (0.06-0.12 nkat g(-1), p < 0.05, 0.26-0.44 nkat g(-1), p < 0.05 and 1.79-2.33, p < 0.05, respectively), macroscopy and plasma thiols remained unchanged. Microdialysis is useful in monitoring gastric ischemia, metabolic monitoring being superior to the (3)H(2)O efflux technique. The results question the efficacy of the utilized model to produce standardized major gastric damage.
Keywords: ischemie; Microdialysis; Water; Rats; tritium; Rats, Wistar; Animals; Male; žaludeční sliznice; Tritium; mikrodialýza; zvířata; Gastric Mucosa; mužské pohlaví; Ischemia; potkani Wistar; krysa rodu Rattus; voda